The role of the androgen receptor as a driver and mitigator of cellular stress - Doultsinos, D; Mills, I (BioScientifica, 2020)
Prostate cancer is a high-incidence male cancer, which is dependent on the activity of a nuclear hormone receptor, the androgen receptor (AR). Since the AR is required for both normal prostate gland development and for prostate cancer progression, it is possible that prostate cancer evolves from perturbations in AR-dependent biological processes that sustain specialist glandular functions. The archetypal example of course is the use of PSA, an organ-type specific component of the normal prostate secretome, as a biomarker of prostate cancer. Furthermore, localised prostate cancer is characterised by a low proliferative index and a heterogenous array of somatic mutations aligned to a multifocal disease pattern. We and others have identified a number of biological processes that are AR-dependent and represent aberrations in significant glandular processes. Glands are characterised by high-rates of metabolic activity including protein synthesis supported by co-dependent processes such as glycosylation, organelle biogenesis and vesicle trafficking. Impairment in anabolic metabolism, protein folding and processing will inevitably impose proteotoxic and oxidative stress on glandular cells, and in particular, luminal epithelial cells for which secretion is their primary function. As cancer develops there is also significant metabolic dysregulation including impaired negative feedback effects on glycolytic and anabolic activity under conditions of hypoxia and heightened protein synthesis due to dysregulated PI 3-kinase/mTOR activity. In this review we will focus on the components of the AR regulome that support cancer development as well as glandular functions focussing on the unfolded protein response and on regulators of mTOR activity.